2010
DOI: 10.1007/s10620-010-1411-2
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin for the Treatment of Clostridium difficile Infection: A Review

Abstract: Clostridium difficile infection (CDI) has increased sharply in incidence, mortality rate, and burden on the healthcare system over the past decade. Therefore, novel treatment modalities have been developed, including intravenous immunoglobulin (IVIG). The level of immune response to Clostridium difficile colonization is the major determinant of the magnitude and duration of clinical manifestations. This effect is mediated predominantly by serum IgG anti-toxin A antibodies. Based on this finding, anti-toxin A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 59 publications
1
51
0
1
Order By: Relevance
“…Th us, there has been interest in immune approaches to treat both severe (refractory) and recurrent RCDI. Publications to date on IVIG to treat RCDI in humans include six case reports and six small case series with varied patient inclusions (severe and recurrent), ages, doses of therapy used, and duration of therapy among other parameters ( 124,125 ). Many patients also received concomitant standard therapy, making interpretation of effi cacy diffi cult.…”
Section: Treatment Of ≥ 3 CDI Recurrencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Th us, there has been interest in immune approaches to treat both severe (refractory) and recurrent RCDI. Publications to date on IVIG to treat RCDI in humans include six case reports and six small case series with varied patient inclusions (severe and recurrent), ages, doses of therapy used, and duration of therapy among other parameters ( 124,125 ). Many patients also received concomitant standard therapy, making interpretation of effi cacy diffi cult.…”
Section: Treatment Of ≥ 3 CDI Recurrencesmentioning
confidence: 99%
“…Passive immunizations with IVIG have been reported to be successful in several small series, including both children and adults. A recent review concluded that the grade of evidence is weak, given the lack of RCTs ( 125 ). One exception may be patients with hypogammaglobulinemia, which is common in patients following solid organ transplants, and may predispose to CDI.…”
Section: Treatment Of ≥ 3 CDI Recurrencesmentioning
confidence: 99%
“…In an early case series of five children with relapsing CDI and low antitoxin antibody levels, intravenous immunoglobulin (IVIG) treatment resulted in resolution of their symptoms in association with an increase in antitoxin antibody levels (Leung et al, 1991). Since that time, IVIG has been used to treat many cases of severe or refractory CDI with mixed results (Abougergi et al, 2010;O'Horo & Safdar, 2009;Wilcox, 2004). Different doses of IVIG (150-400 mg kg 21 ) administered at varying frequencies (one to three doses), with or without adjunctive treatment with oral anti-C. difficile antibiotics, have produced varying results.…”
Section: The Need To Target Both Toxin a And B For Effective Immunothmentioning
confidence: 99%
“…Likewise, there is no standardized algorithm for its use. Most recently, Abougergi et al (2010) reported a high mortality rate (57 %) in 21 patients treated with IVIG for severe CDI. The authors found that higher Acute Physiology and Chronic Health Evaluation II (APACHE II) scores on the day of IVIG infusion were significantly associated with higher mortality.…”
Section: The Need To Target Both Toxin a And B For Effective Immunothmentioning
confidence: 99%
“…There are no randomized controlled trials showing a benefit of IVIG for CDI [Abougergi et al 2010]. It is believed that the mechanism of action for IVIG may include the presence of antibodies against C. difficile toxin A and toxin B Abougergi and Kwon, 2011].…”
Section: Other Medication Regimensmentioning
confidence: 99%